Pengembangan Ekowisata Berbasis Kesesuaian dan Daya Dukung Kawasan Pantai (Studi Kasus Pulau Marsegu Kabupaten Seram Bagian Barat) - Henderina Lelloltery; Satyawan Pujiatmoko; Chafid Fandelli; M. Baiquni (Universitas Pattimura, 2016)
This study aimed to determine the suitability of land and the carrying capacity of the coastal area for ecotourism development in the Nature Tourism Park (TWA) of Marsegu Island. The method used is survey method, with primary and secondary data collection through observation technique. Primary data collection includes the taking of aquatic environmental data, the physical environment of the coast, the area used for tourism activities and the time spent by tourists in the coastal area. Data analysis using coastal suitability index and coastal carrying capacity. Area of ​​white sandy occupies the eastern part of the central part to the north of Marsegu Island with a length of 1.68 km. White sandy beaches with a 20-30 m wide beach provide space for a variety of tourist activities, supported by beautiful natural sea scenery, and high water brightness (90 %), low current velocity (0,16 m/sec) causing this beach can be a promising tourist destination. The result of the analysis of the index of the suitability of coastal ecotourism shows that the white sandy area of ​​Marsegu Island is